2019
DOI: 10.1111/ped.13801
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and vitamin D status in children in Asia

Abstract: Dental caries and vitamin D inadequacy are known to affect children worldwide. Vitamin D has a vital role in tooth formation. There is growing evidence linking suboptimal serum vitamin D level with dental caries in children. This paper reviews the literature on both the prevalence of dental caries and of vitamin D deficiency in children in four Asian regions, discusses their associated risk factors, and reviews the global evidence on the association between dental caries and vitamin D in children. Caries preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 75 publications
0
59
0
Order By: Relevance
“…The difference might be due to different cultural factors and religious behaviors. Girls in Muslim countries with traditional dress have less sun exposure than boys, and boys tend to play outside and produce more vitamin D (14,16). Young age of children has often been found to be a potential risk factor for vitamin D deficiency and insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference might be due to different cultural factors and religious behaviors. Girls in Muslim countries with traditional dress have less sun exposure than boys, and boys tend to play outside and produce more vitamin D (14,16). Young age of children has often been found to be a potential risk factor for vitamin D deficiency and insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Chhonkar et al also showed that vitamin D deficiency was a risk factor both for the incidence and severity of ECC in children aged 3-6 years (24). This relationship between vitamin D and ECC may be explained by the mineralization and antibacterial function of vitamin D. On the one hand, vitamin D deficiency can induce defective tooth mineralization, resulting in dentin and enamel defects, which can increase the risk of dental caries (16). On the other hand, vitamin D can induce certain antimicrobial peptides that protect against oral pathogens, such as defensins and cathelicidins (25).…”
Section: Discussionmentioning
confidence: 99%
“…Low maternal prenatal vitamin D concentrations was identified as a risk factor in one Canadian study (50). Since then, other investigators have also identified that vitamin D levels and prenatal vitamin D intake are associated with increased risk for ECC (7072). In the few years it has been revealed that children with S-ECC are more likely to have lower serum levels of vitamin D, lower iron concentrations, and be both ID and have IDA than caries-free children (22, 23, 49).…”
Section: Discussionmentioning
confidence: 99%
“…ECC has a number of causes and develops as a reaction to a combination of various socio-demographic and behavioural factors [8]. Some studies have shown an association of low vitamin D levels and dental caries in children, while others have not shown any correlation or the association [4,5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. There is clinical evidence of the association of vitamin D deficiency with dental caries in the primary dentition among Canadian populations; they are at risk of vitamin D deficiency due to high latitude geographical location [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various caries-protective factors, such as calcium, inorganic phosphate, pH-increasing substances and antimicrobial agents, are present in saliva. Hence, vitamin D deficiency is an important environmental factor in predisposition to dental caries [4,5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%